Evaluating AI Tools in English Language Learning for Tourism: Insights from Applied Linguistics - I Nengah Laba; Ni Putu Chrisma Dewi (Denpasar Institute, 2024)
This study examines the usefulness of AI technologies in addressing the linguistic and pragmatic abilities required for English Language Teaching (ELT) in the tourism industry. Using a qualitative content analysis approach, the study assesses important aspects, strengths and weaknesses of widely used AI language learning Tools, Duolingo and ELSA Speak. The results show that although these tools are excellent at offering accessibility, adaptive learning pathways, and individualized feedback, they frequently lack industry-specific information, cultural sensitivity, and collaborative learning opportunities—all of which are vital for the tourism industry. These two widely used artificial intelligence (AI) technologies for learning foreign languages in Indonesia only concentrate on grammatical correctness; they fall short in addressing contextualized conversation and intercultural communication in tourism contexts. By bridging the gap between educational ideas and technology, this research advances applied linguistics by providing useful suggestions for educators, curriculum developers, and AI tool creators. Future research should focus on integrating intercultural communication training into AI tools, evaluating their long-term impact on tourism learners’ professional performance and exploring ethical considerations in advancing applied linguistics tailored to professional domains like tourism.